The Axial Hartree-Fock plus BCS Code SkyAx - Reinhard, Paul-Gerhard; Schuetrumpf, B.; Maruhn, J. A. (Computer Physics Communications, 2021)
The nuclear mean-field model based on Skyrme forces can predict a variety of properties of nuclear ground states. We present the Code SKYAx solving the Hartree-Fock equations in two spatial dimensions assuming axial symmetry. Pairing can be included in the BCS approximation. The code is implemented with a view on computational speed.
CRIS-Team WoS Importer:2020-11-27